The Peruvian Traditions: expressions of the world of the life - Arista Montoya, Luis Alberto (2019)
The Peruvian Traditions of Ricardo Palma express the historical tension between the viceregal world that refuses to pass away and the systemic world whose necessities are militarily imposed at first, and subsequently politically proposed through the establishment of new republican institutions.